(untitled) (Research, Society and Development, 2021)
The Brazilian law N° 12.587/12 on urban mobility, currently in effect, aims to ensure the improvement of accessibility, and the trafficability of people and cargo in cities, as well as integrate transport modes, and study mechanisms for infrastructure management. Cities with a population of more than 20,000 had to create their urban mobility plans, according to the requirements of the Ministry of the City. The objective of the plan is to conceive projects that aim to mitigate operational and functional problems in the transportation network within the municipalities. One of these cities that is creating a mobility plan is Anápolis-GO, where its plan includes the implementation of bus lanes on the main avenues of the municipality. In these corridors, there was the substitution of the flexible pavement by slabs of PCC (Portland cement concrete), at the boarding and alighting points, due to the sudden braking events and occasional acceleration. Given this scenario, the study aimed to analyze the stopping distance at these locations, as a function of road speed and braking rate, to assess whether the length of these slabs would be sufficient to what was proposed. In addition, it was sought to monitor the pavement against the performance of the PCC slabs, given the incident loads of braking and acceleration, as well as the performance of the flexible pavement, predicting the possible consequences and/or pathologies that may occur due to the operation, since the existing traffic in the corridors should be compatible with that of a high-speed road.